Solar radiation and productivity in India- I: Potential productivity (MAUSAM, 1986)
The efficiency with which the plants store solar energy was determined and expressed as the product of seven factors describing the dependence of dry matter production on latitude and season, cloudiness and aerosol contents of the atmosphere, on the spectral composition of the radiation, on the quantum. need of the photochemical process, on leaf area index and leaf arrangement, on the concentration of carbon dioxide In the canopy and diffusion resistance of leaves, and on the fraction c f the assimilates used in respiration.The potential and net dry matter productivity of different crops grown between 8 and.30° latitudes in India shows that the efficiencies of radiation interception, diffusion and respiration .provide the environment constraints. These efficiencies are also influenced by the canopy architecture of  crops in terms of the distribution of foliage densities and inclination index of foliage densities.